Elevated glucocorticoid alters the developmental dynamics of hypothalamic neurogenesis in zebrafish - Helen Eachus; Min-Kyeung Choi; Anna Tochwin; Johanna Kaspareit; May Ho; Soojin Ryu (Communications Biology, 2024)
Abstract Exposure to excess glucocorticoid (GC) during early development is implicated in adult dysfunctions. Reduced adult hippocampal neurogenesis is a well-known consequence of exposure to early life stress or elevated GC, however the effects on neurogenesis during development and effects on other brain regions are not well understood. Using an optogenetic zebrafish model, here we analyse the effects of GC exposure on neurogenesis during development in the whole brain. We identify that the hypothalamus is a highly GC-sensitive region where elevated GC causes precocious development. This is followed by failed maturation and early decline accompanied by impaired feeding, growth, and survival. In GC-exposed animals, the developmental trajectory of hypothalamic progenitor cells is strikingly altered, potentially mediated by direct regulation of transcription factors such as rx3 by GC. Our data provide cellular and molecular level insight into GC-induced alteration of the hypothalamic developmental trajectory, a process crucial for health across the life-course.